A computational study of the electronic properties, ionic conduction, and thermal expansion of Sm1−xAxCoO3 and Sm1−xAxCoO3−x/2 (A = Ba2+, Ca2+, Sr2+, and x = 0.25, 0.5) as intermediate temperature SOFC cathodes. Issue 21 (17th May 2017) - Olsson, Emilia; Aparicio-Anglès, Xavier; de Leeuw, Nora H.
Abstract : Substitutional doping of Ca 2+, Sr 2+, and Ba 2+ on the Sm-site in SmCoO3 is reported to improve both electronic and ionic conductivities for applications as solid oxide fuel cell (SOFC) cathodes. Abstract : The substitutional doping of Ca 2+, Sr 2+, and Ba 2+ on the Sm-site in the cubic perovskite SmCoO3 is reported to improve both electronic and ionic conductivities for applications as solid oxide fuel cell (SOFC) cathodes. Hence, in this study we have used density functional theory (DFT) calculations to investigate dopant configurations at two different dopant concentrations: 25 and 50%. To preserve the electroneutrality of the system, we have studied two different charge compensation mechanisms: the creation of oxygen vacancies, and electronic holes. After examining the electronic structure, charge density difference, and oxygen vacancy formation energies, we concluded that oxygen vacancy charge compensation is the preferred mechanism to maintain the electroneutrality of the system. Furthermore, we found that the improvement of the electronic conduction is not a direct consequence of the appearance of electron holes, but a result of the distortion of the material, more specifically, the distortion of the Co–O bonds. Finally, molecular dynamics were employed to model ionic conduction and thermal expansion coefficients. It was found that all dopants at both concentrations showed high ionic conduction comparable to experimental results.